A Method of Strategic Evaluation for Perovskite-Based Flexible Solar Cells - Balo, Figen; Sua, Lutfu S. (CRC Press, 2022)
For the future generation of solar cells, one of the most favorable materials is perovskites. In portable electronics, perovskite-based flexible photovoltaics have attracted significant attention owing to their potency. Power transformation performance comparable to existing industries, such as cadmium telluride and silicon, has been made possible by perovskite films. Their consistency is continuously developing, and it is not hard to think that it will soon meet market demands. By different low-temperature production methodologies and the electrode and interface materials, the performance has surpassed 18% because of the high quality of flexible perovskite solar cells. In the market, there is a wide range of photovoltaic cells. In recent years, new-generation photovoltaic cells from diverse materials have taken their place in the market. In a photovoltaic cell, the primary operating characteristics are efficacy, area, and density characteristics. For perovskite-based flexible solar cells, this study aims to determine the photovoltaic effectiveness and compare the photovoltaic cells manufactured in various kinds with respect to primary operating characteristics. © 2022 selection and editorial matter,[Ram K. Gupta, Tuan Anh Nguyen; individual chapters, the contributors.